PREPARATION AND EVALUATION OF CLOTRIMAZOLE NANOSTRUCTURED LIPID CARRIER FOR TOPICAL DELIVERY - PRACHI B. SHEKHAWAT, (International Journal of Pharma and Bio Sciences, 2013)
The purpose of this study was to prepare Clotrimazole loaded nanostructured lipid carriers (CM-NLC) effective for topical delivery of clotrimazole (CM) by hot homogenization method. Stearic acid as solid lipid, Oliec acid as Liquid lipid, combination of four types of surfactants: Tween 80, Poloxamer-188, Sodium lauryl sulphate (SLS) and Lecithin were used to stabilize NLC dispersion. CM-NLC were characterized by laser diffraction and all the NLC dispersions exhibited average size between 200 and 300 nm. Transmission electron microscopy studies showed that the CM-NLC formulation had a spherical shape. All the formulations had high entrapment efficiency. DSC analysis showed that CM was dispersed in NLC in an amorphous state. The penetration of Clotrimazole from the CM-NLC formulations into cadaver skins was evaluated in vitro using Franz diffusion cell. The CM-NLC formulations could significantly increase the accumulative uptake of CM in skin over the marketed gel and showed a significantly enhanced skin targeting effect. These results indicate that the studied CM-NLC formulation with skin targeting may be a promising carrier for topical delivery of clotrimazole (CM).